The effects of serum, lithium, ethacrynic acid, and a low external concentration of potassium on specific [3H]-ouabain binding to human lymphocytes after incubation for 3 days. - Rapeport, W; Aronson, J; Grahame-Smith, D; Harper, C (1986)
We have quantified specific [3H]-ouabain binding sites in normal human lymphocytes, and have measured the changes in the numbers of those sites which occur in response to various stimuli. We have confirmed previous findings that incubation for 72 h in the presence of fetal calf serum causes an increase in [3H]-ouabain binding, and that this does not occur if the cells are incubated in fetal calf serum which has first been dialysed. During incubation of the lymphocytes for 3 days in the presence of dialysed fetal calf serum each of the following stimuli caused an increase in specific [3H]-ouabain binding: addition of ethacrynic acid (1 mumol l-1), addition of lithium (1 mmol l-1), and reduction of the external potassium concentration (to 0.75 mmol l-1). By analogy with the similar results in HeLa cells reported by others, we suggest that the increase in [3H]-ouabain binding may, in the case of ethacrynic acid and the reduction of the external potassium concentration, be initiated by an increase in the intracellular sodium concentration. The mechanisms whereby fetal calf serum and lithium cause an increase in [3H]-ouabain binding are not clear.